2006
DOI: 10.1248/jhs.52.63
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Level-Dependent Alterations in Urinary Excretion of Thiol Compounds Caused by L-Methionine Supplement in Mice

Abstract: To determine whether alterations in the L-methionine metabolism depend on nutritional conditions such as dietary protein levels, the effects of an L-methionine supplement for a protein-deficient diet on the urinary excretion of low molecular weight thiol compounds were compared to those of the supplement for an adequate protein diet. Although urinary concentrations of L-cysteine and L-homocysteine were increased by the L-methionine supplement irrespective of the dietary protein levels, the levels of increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that the fate of MeHg is affected by dietary levels of protein and sulfur amino acids, [28][29][30][31][32][33] through the alterations in the metabolism of thiol compounds such as GSH 28,29,34,35) and in the amino acid transport. 29,31,32,34) Interestingly, a dietary Met supplement to the refined diet increased Hg accumulation in the liver and decreased that in the kidney regardless of dietary protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the fate of MeHg is affected by dietary levels of protein and sulfur amino acids, [28][29][30][31][32][33] through the alterations in the metabolism of thiol compounds such as GSH 28,29,34,35) and in the amino acid transport. 29,31,32,34) Interestingly, a dietary Met supplement to the refined diet increased Hg accumulation in the liver and decreased that in the kidney regardless of dietary protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…9,[15][16][17][18][19] In contrast, in the hairy and hairless mice in this study, there might be sexdependent differences in the alterations in those fac- In conclusion, the fate of MeHg markedly differs between mice with or without hair, probably due to important differences in metabolism and not to the presence or absence of hair as an excretion route. …”
Section: Fig 1 Time-dependent Changes In Tissue and Excreted Hg In mentioning
confidence: 67%
“…[2][3][4][5][6][7][8][9][10][11] We have revealed that dietary levels of protein and sulfur amino acids are an important factor on the fate and toxicity of MeHg using rodents fed on a 24.8% protein diet (normal protein diet, NPD), a 7.5% protein diet (low protein diet, LPD) or either diet supplemented with sulfur amino acids. [12][13][14][15][16][17][18] In these experiments, the dietary modifications markedly altered the metabolism of low molecular weight thiol compounds including GSH, 12,13,19,20) and the alterations have been suggested to be one reason for the marked differences in the fate of MeHg. In contrast, there are only a few reports revealing the influence of nutritional conditions such as dietary protein deficiency on the fate and toxicity of Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%